2007
DOI: 10.1088/1742-6596/59/1/122
|View full text |Cite
|
Sign up to set email alerts
|

UV, visible and IR laser interaction with gelatine

Abstract: In this work we investigate the effects on gelatine films of nanosecond pulsed laser irradiation at different laser wavelengths from the UV to the IR at 248, 266, 355, 532 and 1064 nm. We compared gelatines differing in gel strength values (Bloom 75 and 225) and in crosslinking degree. Formation of bubbles at the wavelengths in the UV (248 and 266 nm), melting and resolidification at 355 nm, and formation of craters by ablation in the VIS and IR (532 and 1064 nm) are the observed morphological changes. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
4
19
0
Order By: Relevance
“…3. These bands are present in the spectra of all gelatine types explored and are assigned to the aromatic amino acid residue tyrosine (short wavelength) and its dimeric species dityrosine (long wavelength) formed by two tyrosine units when they are in close proximity [18,24]. Upon UV irradiation with ns pulses, and at all wavelengths with fs pulses, a general increase of fluorescence yield is observed and, more importantly, the relative intensity of the two bands I 425 /I 320 always increases of about a factor of 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. These bands are present in the spectra of all gelatine types explored and are assigned to the aromatic amino acid residue tyrosine (short wavelength) and its dimeric species dityrosine (long wavelength) formed by two tyrosine units when they are in close proximity [18,24]. Upon UV irradiation with ns pulses, and at all wavelengths with fs pulses, a general increase of fluorescence yield is observed and, more importantly, the relative intensity of the two bands I 425 /I 320 always increases of about a factor of 3.…”
Section: Resultsmentioning
confidence: 99%
“…In recent works, pulsed laser submicron foam formation has been demonstrated in gelatine and other biopolymers [15][16][17][18] using UV wavelengths and nanosecond (ns) pulses. In the following, investigations concerning aspects of the interaction of ns and fs laser pulses with gelatine films are presented: in particular, examination of the irradiated areas by scanning electron microscopy (SEM) and assessment of the chemical modification by laser induced fluorescence (LIF) measurements on the substrates following irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, their actual absorption coefficients are given as functions of their concentrations (C), and in plant biochemistry the specific absorption coefficient (a) is normally used, which is absorption coefficient per concentration and has units of cm 2 /mg. Owing to this difference, we converted the absorption coefficient data of water to the specific absorption coefficient by dividing it by the density of water (q w ¼ 1 g/cm 3 ). The optical properties of plant leaves considering leaf mesophyll structures have been studied mainly for remote sensing applications.…”
Section: Theoretical Investigation Of Grass Optical Propertiesmentioning
confidence: 99%
“…Pulsed lasers, especially short pulse lasers, have been proved to be an efficient way to process not only common engineering materials but also hard-to-process biomaterials, such as heart tissue, teeth, and cornea. 1 Even some researchers studied laser interaction with cellulose, gelatin and papers [2][3][4] for possible practical applications. In spite of its huge potential importance in many disciplines, however, laser interaction with plant leaves have not been studied to date.…”
mentioning
confidence: 99%
“…More recently Lazare et al 8,21 have reported on the surface foaming of collagen and other biopolymers by KrF laser ablation in the photomechanical regime indicating that the surface microfoam is the result of a thermal mechanism assisted by the tensile component of the laser induced photoacustic transient wave. Initial results on the morphological modifications induced on gelatine films by nanosecond pulsed laser irradiation at different laser wavelengths from the UV to the IR have also been recently reported 22 .…”
Section: Introductionmentioning
confidence: 97%